Identification of a wza-like gene involved in capsule biosynthesis, pathogenicity and biofilm formation in Riemerella anatipestifer. (June 2017) - Yi, Haibo; Yuan, Biao; Liu, Jibin; Zhu, Dekang; Wu, Ying; Wang, Mingshu; Jia, Renyong; Sun, Kunfeng; Yang, Qiao; Chen, Shun; Liu, Mafeng; Chen, Xiaoyue; et al.
Abstract: Duck infectious serositis is the most serious bacterial disease of ducks. It is caused by Riemerella anatipestifer (RA) infection. The capsule plays an important role in virulence of many pathogenic bacteria. In addition, the capsule has some key biological features. However, few studies have explored the characteristics of the RA capsule. In this study, we mainly constructed a capsular mutants of RA by inactivating the wza gene using homologous recombination. We found that the mutant was failed to produce a capsule layer. The mutant was less resistant to killing by the host complement or by desiccation and oxidative stress. Furthermore, the mutant strain was more hydrophobic, more able to auto-aggregate and underwent increased biofilm formation. Moreover, the mutant was less virulent than the wild-type in vivo studies. In summary, we found that the RA capsule was involved in the desiccation and oxidative stress, surface hydrophobicity, complement-mediated killing, biofilm formation, and virulence. Highlights: Riemerella anatipestifer wza gene was responsible for the assembly of the CPS but not for that of the LPS-O-antigen. wza gene is a virulence gene. The product of wza is resistant to the serum killing. wza gene is involved in hydrophobic, auto-aggregation and biofilm formation. wza is also involved in other biological features of Riemerella anatipestifer .